Hubungan Karakteristik Individu dan Sanitasi Lingkungan Terhadap Keberhasilan Pengobatan Tuberculosis di RSUD Bengkalis - Ikhwan Resmala Sudji; Solehan Solehan; Dewi Yudiana Shinta; M Diki Juliandi (Pelantar Press, 2024)
Mycobacterium tuberculosis is a pathogenic bacterium that is the causative agent of tuberculosis. The treatment of tuberculosis is a lengthy process that may induce boredom and lead to the cessation of medication in patients, which can result in the development of bacterial resistance to multiple anti-tuberculosis drugs. Many factors affected the success of tuberculosis treatment include individual characteristics such as age, education, occupation, and environmental conditions such as occupancy density, ventilation, lighting and floor condition. The objective of the study was to know correlation between individual characteristic and home environment with the success of tuberculosis treatment. The observational retrospective and analytics design were applied, which the research population were 30 individual tuberculosis patients who have been regularly without stop taking antibiotics for 6 months or more at the Bengkalis District Hospital. The results demonstrated that all participant have taken tuberculosis antibiotics drugs for more than 6 months and GeneXpert results confirmed 2 patients (6,7%) exhibited positive results for Mycobacterium tuberculosis, and 28 patients (93,3%) exhibited negative results. The individual characteristic such as education level, occupation and enveromental sanitation related to unsuccessful tuberculosis treatment. The findings of this study indicate a need for further examination of the presence of Mycobacterium tuberculosis in patients who have completed treatment, with the objective of ensuring the absence of Mycobacterium tuberculosis in the patient's body.